1995
DOI: 10.1159/000276773
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem for Prevention of Acoustical Trauma during Otologic Surgery

Abstract: 100 patients were tested in a prospective, randomized, double-blinded study to assess the perioperative efficacy of a calcium channel blocker (diltiazem) in preventing acoustical trauma during otologic surgery. The patients were randomly divided into a therapy group (diltiazem) and a control group (placebo). Bone conduction hearing thresholds were examined preoperatively and again 1 day and 3 months postoperatively. Frequency-dependent changes in postoperative bone conduction and the number of patients with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some guinea pig studies showed that diltiazem had a protective effect against acoustic injury Maurer et al 1999) and showed a tendency to reduce the acoustic trauma caused by drilling during otologic surgery in humans (Maurer et al 1995). On the other hand, Boettcher reported that diltiazem did not protect the cochlea from noiseinduced hearing loss in gerbils (Boettcher 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Some guinea pig studies showed that diltiazem had a protective effect against acoustic injury Maurer et al 1999) and showed a tendency to reduce the acoustic trauma caused by drilling during otologic surgery in humans (Maurer et al 1995). On the other hand, Boettcher reported that diltiazem did not protect the cochlea from noiseinduced hearing loss in gerbils (Boettcher 1996).…”
Section: Discussionmentioning
confidence: 99%